Benefits of an Immunogenic Personalized Neoantigen Nanovaccine in Patients with High‐Risk Gastric/Gastroesophageal Junction Cancer (Adv. Sci. 1/2023). Issue 1 (4th January 2023) - Liu, Qin; Chu, Yanhong; Shao, Jie; Qian, Hanqing; Yang, Ju; Sha, Huizi; Cen, Lanqi; Tian, Manman; Xu, Qiuping; Chen, Fangjun; Yang, Yang; Wang, Weifeng; et al.
Abstract : Nanovaccine In article number 2203298, Baorui Liu, Jia Wei, and co‐workers prepare a personalized neoantigen nanovaccine (PNVAC) which spatially displays impressively enhanced lymph nodes trafficking capacity, and functionally induces more mature dendritic cells (DCs), neoantigen‐specific T cells, and memory effector T cells. The PNVAC demonstrates superior protective efficacy against advanced gastric cancer recurrence and longer survival in preclinical studies and a phase I clinical trial.